Update on vasculitis: overview and relevant dermatological aspects for the clinical and histopathological diagnosis - Part II, - Thâmara Cristiane Alves Batista Morita; Paulo Ricardo Criado; Roberta Fachini Jardim Criado; Gabriela Franco S. Trés; Mirian Nacagami Sotto (Sociedade Brasileira de Dermatologia, 2020)
Abstract Vasculitis is a group of several clinical conditions in which the main histopathological finding is fibrinoid necrosis in the walls of blood vessels. This article assesses the main dermatological aspects relevant to the clinical and laboratory diagnosis of small- and medium-vessel cutaneous and systemic vasculitis syndromes. The most important aspects of treatment are also discussed.